Correction of Adverse Response to Suxamethonium of Susceptible Pigs. Issue 5847 (27th January 1973) - Lister, David
Abstract : The adverse response to suxamethonium in susceptible pigs has been shown to be associated with changes in serum free thyroxine index. Pyrexia and acidosis can be controlled by the cautious administration of L-triiodo-thyronine (T-3). Successful correction has been achieved in eight episodes, and in six of these, where it was intended, rapid, uneventful, and complete recovery occurred.